2021
DOI: 10.1364/oe.438286
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast laser-induced strain waves in thin ruthenium layers

Abstract: We report on the time-dependent optical diffraction from ultra-high frequency laser-induced acoustic waves in thin layers of ruthenium deposited on glass substrates. We show that the thermo-optic and strain-optic effects dominate the optical response of Ru layers to a traveling longitudinal strain wave. In addition, we show the generation and detection of acoustic waves with a central frequency ranging from 130 GHz to 750 GHz on ultra-thin layers with thicknesses in the range of 1.2 - 20 nm. For these ultra-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…where d and f are the film thickness and breathing mode frequency [16,22]. It has been shown that thin Cr films on the Si substrate in Figure 2c have broader peaks than the SiO 2 substrate in Figure 2d, which is in accordance with the fact that the acoustic impedance mismatch of Cr-Si is larger than that of Cr-SiO 2 .…”
Section: Typical Acoustic Signalssupporting
confidence: 66%
See 2 more Smart Citations
“…where d and f are the film thickness and breathing mode frequency [16,22]. It has been shown that thin Cr films on the Si substrate in Figure 2c have broader peaks than the SiO 2 substrate in Figure 2d, which is in accordance with the fact that the acoustic impedance mismatch of Cr-Si is larger than that of Cr-SiO 2 .…”
Section: Typical Acoustic Signalssupporting
confidence: 66%
“…Therefore, the result of vaporized Cr films on the Si substrate are not shown in Figure 3 and reported in this study. Figure 3c show that the out-of-plane elastic modulus C33 decrease with the decrease of the film thickness due to the thin-film softening effect, which has been reported in thin films of Au [12], Ni [17], and Ru [22]. For comparison, we calculated the elastic modulus along the <110> directions using the known Cij of monocrystal Cr by 𝐶 = (𝐶 + 𝐶 + 2𝐶 )/2 [26].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, laser‐induced acoustic waves can be used to introduce time‐(in)dependent modification for various applications, such as 2D material time crystals. [ 187 ] Additionally, light polariton propagation in 2D materials can be explored to produce self‐induced waveguide writing. [ 188 ]…”
Section: Perspectivesmentioning
confidence: 99%
“…For example, laser-induced acoustic waves can be used to introduce time-(in)dependent modification for various applications, such as 2D material time crystals. [187] Additionally, light polariton propagation in 2D materials can be explored to produce selfinduced waveguide writing. [188] Further, combining optical modification with other photonic methods, such as near-field optics, micro-and nanoresonators, photonic crystal cavities, and plasmonics, can further boost the performance and tuning of 2D devices, potentially enabling even higher resolutions beyond the diffraction limit, and faster operating or patterning speeds.…”
Section: New Optical Modification Strategiesmentioning
confidence: 99%